English Proficiency and Language Preference: Testing the Equivalence of Two Measures - Gee, Gilbert C; Walsemann, Katrina M; Takeuchi, David T (American journal of public health (1971), 2010)
Objectives. We examined the association of language proficiency vs language preference with self-rated health among Asian American immigrants. We also examined whether modeling preference or proficiency as continuous or categorical variables changed our inferences. Methods. Data came from the 2002–2003 National Latino and Asian American Study (n = 1639). We focused on participants' proficiency in speaking, reading, and writing English and on their language preference when thinking or speaking with family or friends. We examined the relation between language measures and self-rated health with ordered and binary logistic regression. Results. All English proficiency measures were associated with self-rated health across all models. By contrast, associations between language preference and self-rated health varied by the model considered. Conclusions. Although many studies create composite scores aggregated across measures of English proficiency and language preference, this practice may not always be conceptually or empirically warranted.